Cambios relevantes en la presentación de estados financieros del nuevo marco normativo para pymes en Colombia. - Soledad Estupiñan, Karen Eliana; Arévalo Casas, Juan Diego (Universidad Antonio Nariño, 2021)
The application process to the new accounting regulations under the International Financial Reporting Standards standard, issued by the IASB, and by means of the parameters established by the strategic direction of the application process of the financial reporting accounting standards and the assurance of the Information with international standards issued by the Technical Council of Public Accounting on December 5, 2012 and based on Decree 3022 of December 27, 2013, complies with the parameters established to classify within group 2 of said standards, and will apply IFRS for SMEs.